2018
DOI: 10.3389/fneur.2018.00933
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Ischemic Core ≥70 ml Within 6 h of Symptom Onset May Still Benefit From Endovascular Treatment

Abstract: Background: Large core is associated with poor outcome in acute ischemic stroke (AIS) patients. It is unclear whether endovascular treatment (EVT) could bring benefits to patients with core volume ≥70 ml before treatment. We aimed to compare the impact of EVT with intravenous thrombolysis (IVT) on the outcome in patients with core volume ≥70 ml.Methods: We included consecutive anterior circulation AIS patients who underwent MR or CT perfusion within 6 h post stroke onset, which revealed a core ≥70 ml before re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Amongst 622 studies screened for inclusion and two records yielded from other sources between 2015 and June 2020, a total of 10 records 3,6,8,[15][16][17][18][19][20][21] with 954 patients with baseline large ischemic volumes were included in our review. See flowchart of studies selection in Figure 1.…”
Section: Literature Review and Study Selectionmentioning
(Expert classified)
See 2 more Smart Citations
“…Amongst 622 studies screened for inclusion and two records yielded from other sources between 2015 and June 2020, a total of 10 records 3,6,8,[15][16][17][18][19][20][21] with 954 patients with baseline large ischemic volumes were included in our review. See flowchart of studies selection in Figure 1.…”
Section: Literature Review and Study Selectionmentioning
(Expert classified)
“…Five studies (71.5%) were from a single center, and six (85.7%) reported a prospective enrolment. Amongst the included studies, six 3,8,16,[19][20][21] totalizing 682 patients had control groups treated with BMT alone, allowing to compare 332 patients who received MT to 350 who received BMT only. Four studies 3,6,15,18 used only MRI, two 8,20 over 90% of MRI and were merged with the MRI group.…”
Section: Literature Review and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al performed a retrospective review and stated that endovascular therapy performed within 6 hours of onset achieved higher reperfusion and recanalization rates compared to IV-tPA. 62 Gligen et al demonstrated similar results in younger patients with large MRI-DWI lesions. 63 Kaesmacher et al were able to show that mechanical thrombectomy in patients with Alberta Stroke Program Early CT Score of 0 to 5 were able to have successful reperfusion, with no increase in the rate of sICH.…”
Section: Treatment Of Large Core Strokesmentioning
confidence: 70%
“…However, this concept came from the studies conducted in patients receiving intravenous thrombolysis whereby a higher rate of symptomatic intracerebral hemorrhage and poorer outcomes can be attributable to malignant profile [1]. Recently, there has been some evidence that patients who present within 6 h with a core volume ≥70 mL may still benefit from EVT, which was potentially related to high reperfusion rates observed in these studies [3]. The SELECT study suggests that there are potential benefits for patients with large cores up to 24 h from the time last known to be well, who were selected based on an Alberta Stroke Program Early CT Score (ASPECTS) of less than 6, or a volume with a relative cerebral blood flow <30% of ≥50 cm 3 on CT perfusion scanning [4].…”
Section: Introductionmentioning
confidence: 99%